Redshift of A1(longitudinal optical) mode for GaN crystals under strong electric field. (19th December 2017) - Gu, Hong; Wu, Kaijie; Zheng, Shunan; Shi, Lin; Zhang, Min; Liu, Zhenghui; Liu, Xinke; Wang, Jianfeng; Zhou, Taofei; Xu, Ke
Abstract: We investigated the property of GaN crystals under a strong electric field. The Raman spectra of GaN were measured using an ultraviolet laser, and a remarkable redshift of the A 1 (LO) mode was observed. The role of the surface depletion layer was discussed, and the interrelation between the electric field and phonons was revealed. First-principles calculations indicated that, in particular, the phonons that vibrate along the [0001] direction are strongly influenced by the electric field. This effect was confirmed by a surface photovoltage experiment. The results revealed the origin of the redshift and presented the phonon property of GaN under a strong electric field.